A representation framework of product–service systems. (23rd January 2020) - Kim, Yong Se
Abstract : Product–service systems (PSSs) have drawn significant attention as a driver for business innovation and manufacturing servitization. A PSS is a system of products and services, supporting networks and infrastructure that are designed to satisfy customer needs and to generate values. In this paper, a representation framework for PSSs with eight spaces of product, customer, value, actor, service, business model, interaction context and time space has been proposed to help compare different PSSs and to support the design process. A PSS repository using the representation framework has been developed. To illustrate the representation method and its utility, 15 industry PSS cases are briefly introduced, and comparisons of these cases using the PSS representation framework and similarity assessments are explained. The utilities of the framework in designing PSSs and in analyzing and planning manufacturing servitization are discussed as well.